Prioritas Media dan Terpaan Informasi Gagal Ginjal Akut pada Anak terhadap Tingkat Kecemasan Ibu Muda @MPASIBAYISEHAT - Gustina, Fenti; Marta, Rustono Farady; Sarasati, Fitri; Chinmi, Maichel; Tjajadi, Octavia Putri; Wahyuddin (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
Abstract (Bahasa Inggris) The study aimed to investigate the impact resulting from the prioritization of information and information exposure on cases of Acute Kidney Injury in Children, specifically examining the level of anxiety among young mothers who follow the Instagram account @mpasibayisehat. This research uses three theories, that is Agenda Setting Theory for variable X1 of prioritization of information; Cultivation Theory for variable X2 of information exposure; and Anxiety and Uncertainty Management Theory for variable Y of level of anxiety. The coefficient analysis results reveal that factor X1 yielded a t-value of 5.350, while variable X2 showed a t-value of 2.729. Additionally, the ANOVA table indicates that the calculated F-value is 219.652. This suggests a significant impact between each independent factor and the dependent factor. Furthermore, collectively, the independent factors also have a significant impact on the dependent variable. In this context, considering the coefficient of determination, the influence of variable X on Y can be measured at a substantial 81.5%. These findings illustrate that the observed influence falls into the category of very high impact. Keywords: Acute Renal Failure, Anxiety Level, Information Priority, Information Exposure, Young Mother